Sex differences in injury during top-level international athletics championships: surveillance data from 14 championships between 2007 and 2014. Issue 7 (24th January 2015) - Edouard, Pascal; Feddermann-Demont, Nina; Alonso, Juan Manuel; Branco, Pedro; Junge, Astrid
Abstract : Background: Injury incidence has been reported for international athletics championships from 2007 to 2012. However, it is unclear whether male or female athletes differ in risk and/or characteristics of injuries. Objective: To compare the incidences and characteristics of injuries that occurred during international athletics championships between female and male athletes. Methods: The national medical team and the local organising committee physicians reported all injuries daily on a standardised injury report form during 14 international championships from 2007 to 2014. Relative risks (RR) of injury, 95% CI and magnitude thresholds were calculated. Results: The rate of injuries per 1000 registered athletes was significantly higher in male (110.3±6.8) than in female (88.5±6.7) athletes (RR=1.25; 95% CI 1.13 to 1.37, small effect size). Male athletes incurred significantly more injuries in the thigh (RR=1.64; 95% CI 1.32 to 2.05, small), lower leg (RR=1.36; 95% CI 1.05 to 1.75, small) and hip/groin injuries (RR=2.26; 95% CI 1.31 to 3.88, moderate), more muscle strains (RR=1.64; 95% CI 1.33 to 2.04, small), cramps (RR=1.81; 95% CI 1.35 to 2.43, small), and especially more thigh strains (RR=1.66; 95% CI 1.25 to 2.19, small), but fewer stress fractures (RR=0.32; 95% CI 0.12 to 0.81, moderate) than female athletes. A higher injury risk of male than of female athletes was observed in sprints (RR=1.32; 95% CI 1.06 to 1.66, small), middle distance runs (RR=1.48; 95% CI 1.06 to 2.06, small), race walks (RR=2.55; 95% CI 1.27 to 5.10, moderate) and jumps (RR=2.13; 95% CI 1.53 to 2.97, moderate). No sex difference was found for cause and severity of injury. Conclusions: Injury risk during international athletics championships differed between female and male athletes for location, type and event groups. Injury prevention strategies should be sex-specific, regarding the differences in injury location and type.